In vitro screening of chilli (Capsicum annuum L.) genotypes for drought tolerance - Sharma, Prashant; Kurubar, A. R.; Tembhurne, B. V.; Paatil, Shekharagouda (Journal of Horticultural Sciences, 2024)
Chilli drought tolerance testing at the germination stage using osmotic polyethylene glycol (PEG) is an alternative method for conducting rapid screening in order to assemble drought tolerant varieties. Under normal and drought conditions, 16 chilli genotypes and 3 levels PEG 6000 @ 5% (-0.3 Mpa), 10% (-0.6 Mpa), 15% (-0.9 Mpa) and control were screened under in vitro for drought tolerance at the seeding stage in completely randomized factorial design with three replications. Among the genotypes tested, UARChH 42, UARChH 43, and Arka Swetha were found as drought-tolerant, indicating their utilization in breeding drought-tolerant genotypes and enhance cultivation in drought-prone regions.
Keywords: Chilli; drought tolerance; PEG treatment; screening